Automatic data-flow graph generation of MPI programs - Silva, R. E.; Pezzi, G.; Maillard, N.; Diverio, T. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2005)
The data-flow graph (DFG) of a parallel application is frequently used to take scheduling decisions, based on the information that it models (dependencies among the tasks and volume of exchanged data). In the case of MPI-based programs, the DFG may be built at run-time by overloading the data exchange primitives. This article presents a library that enables the generation of the DFG of a MPI program, and its use to analyze the network contention on a test-application: the Linpack benchmark. It is the first step towards automatic mapping of a MPI program on a distributed architecture.